CURRICULUM REFORM IN SOUTH AFRICAN HIGHER EDUCATION: EVALUATING POLICY EFFECTIVENESS AND INSTITUTIONAL RESPONSE - Haruna Maama (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
There has been intense scrutiny about the design and delivery of curricular in South Africa higher education institutions. Various policies and laws have been established to ensure that the South African higher education contributes to the transformation agenda of the nation. This study contributes to this debate by examining how the South African higher education policies contributes to the transformation of curriculum to meet contemporary socioeconomic needs. The study employs a morphogenetic approach to explore how existing frameworks, such as the Higher Education Act of 1997 and the White Paper for Post-School Education and Training (2014), have shaped the curriculum design and implementation processes in South African universities. The paper begins by discussing the internationalisation of higher education curricula and highlights the need for graduates to develop global competencies. It further examines the role of the South African internationalisation policy in preparing students for the global economy. The research also addresses how policy gaps, such as the inadequate focus on decolonisation and the lack of alignment with the Fourth Industrial Revolution (4IR), impact the effectiveness of curriculum transformation efforts. The findings reveal that despite numerous policy frameworks and strategic documents, there remains a disconnect between the goals of higher education policies and the practical realities of curriculum design and delivery. This disconnect contributes to the numerous challenges in the higher education sector, manifested through student protests and dissatisfaction with the relevance of academic programs. The paper concludes that a more nuanced approach to curriculum reform is necessary, one that bridges policy intentions with practical outcomes through continuous dialogue among universities, the government, and industry stakeholders.